Evidens pentaksiran sekolah dalam pengajaran Bahasa Arab Sekolah Rendah / Wan Mohd Zuhairi Wan Abdullah - Wan Mohd Zuhairi, Wan Abdullah (2017)
This study aims to explain on how evaluation evidence is managed in classroom teaching. The objective of school assessments in the teaching process is to help students’ learning. Teachers need assessment evidence to assess students’ proficiency and the effectiveness within the process. Teachers' failure to understand, value and manage evidence of school assessments well can cause assessment activities to be just a routine schedule only. This study explores in depths on how the teacher conducts assessment activities and manages evidence of school assessments in primary Arabic teaching in their natural environment. The design of this study uses qualitative case study methods. Four Arabic teachers from four primary schools were selected as research participants. The research participants were selected based on purposive sampling which took into account the teachers' expertise in that particular subject as the main criteria based on information from informants and gate keeper. The researcher was also involved as an observer and research instrument at the location of the study. The collection of data was done by observation, document analysis and interview. Emergent and naturalistic data were filtered and analyzed using Atlas.ti version 7 which involves coding and sub-coding processes for themes and sub-themes to answer research questions. Data analysis were carried out during and after collection of data. The results indicate that the evidence of assessments was well managed by the participants. The management of assessment evidence covers initial assessment planning, identifying strategy, citing, interpreting assessment evidence and reflecting on teaching processes in the classroom. This study has produced a School Assessment Evidence Management Strategy (SPEPS) that helps teachers manage evidence of assessment in their teaching processes. There is also an element of action study in the classroom when the teachers managed evidence of assessment. The management of assessment evidence teaching also includes student-centered approaches, empowerment and promoting peer-to-peer learning. This study supports the assessment of learning activities through the experience from four participants in managing the evidence of school assessments and helping to improve students’ learning. Collecting positive responses from people dealing with education policy, curriculum development, assessment management, teacher education training, school administration, pedagogy, parenting, teacher’s professional development and student’s learning processes are the implications of this study. Hence, the implementation of planning and management of the evidence evaluation are essential in helping teachers to be more effective in their continuous classroom teaching.